2020
DOI: 10.1042/cs20191313
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation: major denominator of obesity, Type 2 diabetes and Alzheimer’s disease-like pathology?

Abstract: Adipose tissue is an active metabolic organ that contributes to processes such as energy storage and utilization and to the production of a number of metabolic agents, such as adipokines, which play a role in inflammation. In this review, we try to elucidate the connections between peripheral inflammation at obesity and Type 2 diabetes and the central inflammatory process. Multiple lines of evidence highlight the importance of peripheral inflammation and its link to neuroinflammation, which can lead to neurode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 265 publications
1
29
0
Order By: Relevance
“…A chronic low-grade inflammation, triggered by nutrient surplus, is a constituent of obesity. Adipose-originated metabolic inflammation develops pari passu with insulin resistance and, as such, is a key element in the metabolic syndrome [ 14 ]. In this study, we found there were no significant differences in serum IL-6, TNF-α, LBP and leptin between MHO and MUO subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A chronic low-grade inflammation, triggered by nutrient surplus, is a constituent of obesity. Adipose-originated metabolic inflammation develops pari passu with insulin resistance and, as such, is a key element in the metabolic syndrome [ 14 ]. In this study, we found there were no significant differences in serum IL-6, TNF-α, LBP and leptin between MHO and MUO subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A chronic low-grade in ammation, triggered by nutrient surplus, is a constituent of obesity. Adiposeoriginated metabolic in ammation develops pari passu with insulin resistance and, as such, is a key element in the metabolic syndrome [12]. In this study, we found there were no signi cant differences in serum IL-6, TNF-α and leptin between MHO and MUO subjects.…”
Section: Discussionmentioning
confidence: 40%
“…A chronic low-grade in ammation, triggered by nutrient surplus, is a constituent of obesity. Adiposeoriginated metabolic in ammation develops pari passu with insulin resistance and, as such, is a key element in the metabolic syndrome [14]. In this study, we found there were no signi cant differences in serum IL-6, TNF-α, LBP and leptin between MHO and MUO subjects.…”
Section: Discussionmentioning
confidence: 41%